Ethical perspectives on the management of COVID-19 pandemic and its impact on mental health - Alarcon, Renato (2020)
.As an essential component of medical work throughout history, Ethics becomes even more prominent in public health emergency situations. After presenting the fundamental ethical principles, and emphasizing their value in the medical care of every human being, the inevitable tensions that their application generates in the diverse contexts of the doctor-patient relationship, are examined. Particular attention must be paid to the distinctions between ethical perspectives of individual cases and those related to public health situations such as the massive emergency triggered by the COVID-1 pandemic. On the basis of recent national and international documents, the unavoidable upcoming of new ethical norms that must include socio-cultural, psychological and legal aspects of a highly significant clinical impact, is discussed.